Trends and outcomes of cardiac arrest and extracorporeal membrane oxygenation during the COVID-19 pandemic in the United States - Joseph Hadaya; Shayan Ebrahimian; Nam Yong Cho; Shineui Kim; Peyman Benharash (PLoS ONE, 2025)
Background The COVID-19 Pandemic challenged the healthcare system worldwide, but its effect on outcomes of cardiac arrest (CA) and extracorporeal membrane oxygenation (ECMO) use are understudied. We examined trends in CA, ECMO use and survival, and evaluated the impact of receiving care during the COVID-19 Pandemic on outcomes following CA. We also evaluated the impact of COVID-19 infection on outcomes following CA. Methods Adults with out-of-hospital (OHCA) or in-hospital cardiac arrest (IHCA) were identified in the 2016−2020 National Inpatient Sample. For primary analysis, CA patients without COVID-19 were divided into Pre-Pandemic and Pandemic time-periods. For secondary analysis, CA patients treated during the Pandemic time-period were divided by COVID-19 infection status. Generalized linear models were used to evaluate associations between Pandemic time-period or COVID-19 infection with in-hospital mortality. Results Of 1,320,020 non-COVID-19 CA patients, 19.1% were managed during the Pandemic. From 2016−2019, CA incidence increased from 696 to 771 per 100,000 hospitalizations, and disproportionately increased to 1,023 per 100,000 hospitalizations by the end of 2020. Mortality for IHCA was stable prior to the Pandemic, but increased from 67.4% to 75.4% by the end of 2020, while mortality for OHCA was stable. ECMO use increased from 2016 to 2019 for OHCA and IHCA, declined during the second quarter of 2020, and recovered to pre-Pandemic levels by the end of 2020. After risk-adjustment, care during the Pandemic was associated with 1.2-fold greater odds of mortality after CA for non-COVID-19 patients. Among 277,975 patients experiencing CA during the Pandemic, 19.6% had concomitant COVID-19 infection. After risk-adjustment, COVID-19 infection was associated with 3.9-fold greater odds of mortality after CA. Conclusion CA incidence and mortality increased during the COVID-19 Pandemic, while ECMO use declined, emphasizing the need to improve care of CA and ECMO patients. COVID-19 patients with CA had dismal outcomes, suggesting no role for ECMO in this population.